Structural competency in global perspective - Carlos Piñones-Rivera; Seth M. Holmes; Michelle Morse; Joel Ferrall; Kavya Nambiar; Ángel Martínez-Hernáez (Global Public Health)
This special issue aims to help fill two critical gaps in the growing literature as well as in practice. First, to bring together scholars and practitioners from around the world who develop, practice, review, and question structural competency with the aim of promoting a dialogue with related approaches, such as Latin American Social Medicine, Collective Health, and others, which have been key in diverse geographical and social settings. Second, to contribute to expanding structural competency beyond clinical medicine to include other health-related areas such as social work, global health, public health practice, epidemiological research, health policy, community organisation and beyond. This conceptual expansion is currently taking place in structural competency, and we hope that this volume will help to raise awareness and reinforce what is already happening. In sum, this collection of articles puts structural competency more rigorously and actively in conversation with different geographic, political, social, and professional contexts worldwide. We hope this conversation sparks further development in scholarly, political and community movements for social and health justice.